1990
DOI: 10.1044/jshd.5502.339
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacusis and Otitis Media in Individuals with Williams Syndrome

Abstract: Williams syndrome is characterized by cardiac defects, varying degrees of physical and developmental delay, stellate eye pattern, possible elevated serum calcium level, and elfin/pixie facial features. A problem perhaps unique to these children is hyperacusis that can be severe enough to disrupt many routine daily activities. Parental questionnaires were used to determine the prevalence of hyperacusis and otitis media in individuals with Williams syndrome. Prevalences of 95% for hyperacusis and 61% for otitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1
6

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 13 publications
8
104
1
6
Order By: Relevance
“…Quando a média dos limiares de desconforto obtidos nas freqüências de 250, 500, 1000, 2000 e 4000 Hz for igual ou inferior a 90 dB NA, há indicação da presença de hiperacusia (5) . Desde a década de 30, pesquisas indicavam a presença de hiper sensibilidade auditiva, associada a outras alterações, como paralisia do nervo facial (6) , pós-estapedectomia (7)(8) , zumbido (9) , síndrome de Williams (10) . Atualmente, sabe-se que a hiperacusia pode ser causada ou acompanhar diversas condições patológicas periféricas (estapedectomia, paralisia de Bell, síndrome de Ramsay Hunt) ou centrais (enxaqueca, depressão, traumatismo craniano leve) (11) .…”
Section: Introductionunclassified
“…Quando a média dos limiares de desconforto obtidos nas freqüências de 250, 500, 1000, 2000 e 4000 Hz for igual ou inferior a 90 dB NA, há indicação da presença de hiperacusia (5) . Desde a década de 30, pesquisas indicavam a presença de hiper sensibilidade auditiva, associada a outras alterações, como paralisia do nervo facial (6) , pós-estapedectomia (7)(8) , zumbido (9) , síndrome de Williams (10) . Atualmente, sabe-se que a hiperacusia pode ser causada ou acompanhar diversas condições patológicas periféricas (estapedectomia, paralisia de Bell, síndrome de Ramsay Hunt) ou centrais (enxaqueca, depressão, traumatismo craniano leve) (11) .…”
Section: Introductionunclassified
“…Seventy-five percent to 95% of children with WS have mild to moderate mental retardation, and about 80% of patients exhibit generalized anxiety disorder and are more likely to have Attention Deficit and Hyperactivity Disorder (ADHD). Large number (74%-95%) of children with WS is sensitive to sounds [31]. Oral, inhalational sedation should be considered for provision of less extensive dental treatment at a younger age to patients with WS as it can help to reduce anxiety and uncooperative behavior and thereby help the patient to cope with the procedure.…”
Section: Medical Considerations In the Dental Treatment Of Children Wmentioning
confidence: 99%
“…Since many adverse reactions to sound occurred prior to 1 year of age, Klein, Armstrong, Greer and Brown (1990) concluded that audiosensitivity was a primary acoustic-evoked phenomenon.…”
Section: Underascertainment Of Deafnessmentioning
confidence: 99%